Monetary economics : policy and its theoretical basis - Bain, K.; Howells, P. G. A. (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2003)
A useful course text for third year modules in monetary economics. The book achieves a balance between theory and practice and enables the student to understand the theoretical basis of monetary economics. It is also distinctive in its concentrated focus on the practice of monetary policy. The authors view money supply as endogenous and central banks as preoccupied with interest rates rather than monetary aggregates, which gives the book a practical and "real world" character.
Includes bibliographical references (p. 474-502) and index.
lje 02/05/13; oif 31/08/15
Loan
Keywords: Monetary policy; Monetary economics